Unravelling meanings in interpretive plurality - Wang, Mengqiao (Nanyang Technological University, 2020)
Studies on the rendition of historical texts are curiously quiet in the entire discipline of translation studies. Interpreting historical text is so challenging that it deserves devotion from this dissertation to raise awareness on revolving and evolving issues. The challenges, namely reclaiming indigenous representations and identity in global historical studies; negotiation and reconciliation of cultural disparities against the effort to enhance the presence of native voices in an off-balance Eurocentric historical discourse setting. Minguo Tongsu Yanyi, a modern historical text written by historian scholar Cai Dongfan who lived through that phase of change, is specially chosen to illustrate how the above problems and issues can be overcome and answered.